Feedforward artificial neural network-based model for predicting the removal of phenolic compounds from water by using deep eutectic solvent-functionalized CNTs - Ibrahim R.K.; Fiyadh S.S.; AlSaadi M.A.; Hin L.S.; Mohd N.S.; Ibrahim S.; Afan H.A.; Fai C.M.; Ahmed A.N.; Elshafie A. (MDPI AG, 2023)
carbon nanotube; phenol derivative; solvent; adsorption; algorithm; chemistry; kinetics; theoretical model; water management; water pollutant; Adsorption; Algorithms; Kinetics; Models, Theoretical; Nanotubes, Carbon; Neural Networks, Computer; Phenols; Solvents; Water Pollutants, Chemical; Water Purification